The effect of organic fertilizers on the biochemical properties of soil contaminated with zinc - J. Wyszkowska; A. Borowik; J. Kucharski; M. Baćmaga; M. Tomkiel; E. Boros-Lajszner (Plant, Soil and Environment, 2013)
This study evaluates the effectiveness of organic fertilizers in restoring the homeostasis of soils contaminated with zinc. The activity of selected enzymes participating in the transformation of carbon, nitrogen, phosphorus and sulfur and the sensitivity of white mustard plants to zinc were analyzed. A greenhouse pot experiment was carried out. Uncontaminated soil served as control. Six organic substances which potentially neutralize the adverse effects of zinc were used: tree bark, finely ground barley straw, pine sawdust, cattle manure, compost and cellulose. It was found that in less contaminated soil (300 mg Zn2+/kg), all of the analyzed organic substances minimized zinc adverse effects on the biochemical properties of soil, including the activity of dehydrogenases, catalase, urease, acid phosphatase, alkaline phosphatase, β-glucosidase and arylsulfatase. In more contaminated soil (600 mg Zn2+/kg), the negative consequences of zinc pollution were effectively mitigated only by cellulose, barley straw and manure. Cellulose had the highest soil restoration potential, as demonstrated by resistance indicator values for different enzymes. Cellulose, compost, manure and straw increased the resistance of white mustard plants to zinc, but only in treatments contaminated with 300 mg Zn2+/kg. Bark and sawdust potentiated zinc toxic effects on mustard plants.